Pengaruh Kinerja Perawat Pelaksana Terhadap Kepuasan Pasien Rawat Jalan Di Pasir Panjang Kota Kupang - Abrao Punef (CHMK Applied Science Journal, 2022)
ABSTRACT The Effect of Implementing Nurse Performance on Outpatient Satisfaction at Pasir Panjang Public Health Center, Kupang City. Background : Customer satisfaction occurs when the needs, desires, expectations of customers can be fulfilled. But in reality there is customer or patient dissatisfaction with the services provided. This happens because the dynamics of patient demands are changing rapidly but they are balanced with the speed of change work patterns and actions of nurses. The impact that often arises due to the poor performance of nurses is patient dissatisfaction and decreased patient interest in using nursing services in that place. Customers feel disappointed if the service received is still below expectations. This study aimed to analyze the effect of nurse performance on outpatient satisfaction at Pasir Panjang Public Health Center, Kupang City. This Study used a quantitative research with a cross sectional design. The sample in this study amounted to 62 respondents. The technique used purposive sampling. This study used a questionnaire as a data collection tool and analyzed by using a simple linear regression test. The results of this study indicated that the performance of the implementing nurses at the Pasir Panjang Public Health Center in Kupang City was in the good category (50.0%), outpatient satisfaction was in the enaugh satisfied category (69.4%). Something else that really affected the performance of the health force, then a very impact on performance, if the work is controlledloss so that the organization’s ultimate goal is not reached. The increased satisfaction of the patient is sought by improving the performance of the nurse in order to keep the ministry good and to restore the fundamental of nursing so that the role and function of the nursing is well accomplished. Keywords: Implementing Nurse Performance, Outpatient Satisfaction